Image perceived as a trigger for innovation and business competitiveness in the tourism sector (Revista revoluciones, 2023)
The projected and perceived image was analyzed as a multidimensional construct that involves cognitive and affective evaluations that allow the formulation of marketing strategies for the innovation of organizational processes. The essay sought to generate knowledge that allows the management of the image as a trigger for innovation and business competitiveness in the tourism sector, allowing the design of a marketing strategy for the innovation of organizational processes. Topics related to: administration, administrative process, marketing and particularly on the structure of the image variable were reviewed. The projected image must be as clear, understandable and close to reality as possible. Ideally, the perceived image corresponds to what the company or tourist destination has wanted to project, since it becomes important for decision-making, and identification of areas of opportunity to improve indicators.
Keywords: administration; perceived image; projected image; innovation; marketing